ISPC Theory of Change: In Brief - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
This Brief presents the ISPC's mandate to serve as an independent advisor to the CGIAR System Council on science and research matters, and outlines the ISPC's vision, mission, goals, and Theory of Change.